2020
DOI: 10.1371/journal.pone.0238385
|View full text |Cite
|
Sign up to set email alerts
|

Replicable simulation of distal hot water premise plumbing using convectively-mixed pipe reactors

Abstract: A lack of replicable test systems that realistically simulate hot water premise plumbing conditions at the laboratory-scale is an obstacle to identifying key factors that support growth of opportunistic pathogens (OPs) and opportunities to stem disease transmission. Here we developed the convectively-mixed pipe reactor (CMPR) as a simple reproducible system, consisting of off-the-shelf plumbing materials, that self-mixes through natural convective currents and enables testing of multiple, replicated, and reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…CMPRs are an inexpensive, space-efficient, and replicable means of simulating distal, stagnant outlets off of risers from hot water recirculation lines ( Spencer et al., 2020 ). PVC, copper, and mild steel plumbing were simulated using sealed four-foot pipe segments composed of either ¾” PVC (Silver-line Plastics, Ashville, NC) (PVC CMPRs), half ¾” PVC and half type M copper pipe (McMaster-Carr, Elmhurst, IL) (copper-PVC CMPRs), or three-inches of ¾” mild steel pipe (McMaster-Carr, Elmhurst, IL) attached to forty-five-inches of ¾” PVC (iron-PVC CMPRs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CMPRs are an inexpensive, space-efficient, and replicable means of simulating distal, stagnant outlets off of risers from hot water recirculation lines ( Spencer et al., 2020 ). PVC, copper, and mild steel plumbing were simulated using sealed four-foot pipe segments composed of either ¾” PVC (Silver-line Plastics, Ashville, NC) (PVC CMPRs), half ¾” PVC and half type M copper pipe (McMaster-Carr, Elmhurst, IL) (copper-PVC CMPRs), or three-inches of ¾” mild steel pipe (McMaster-Carr, Elmhurst, IL) attached to forty-five-inches of ¾” PVC (iron-PVC CMPRs).…”
Section: Methodsmentioning
confidence: 99%
“…CMPR effluent was treated by adding 7.5% sodium hypochlorite bleach (Clorox, Alpharetta, GA) to 10% v/v before disposal. During this period, chemical and biological water quality was profiled to verify the replicability of CMPRs as reported elsewhere ( Spencer et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…There have been several laboratory studies ,, and a field-study aiming to understand how heater design and operation impact opportunistic pathogens. Most studies have found that water usage patterns and water heater design influence the chemical and microbial water quality. ,,, One study compared three configurations of residential electric water heating systemsstandard, recirculation, and tankless heatersin terms of volumes at risk for pathogen growth based on temperature measurements and water quality parameters while operating them at different use patterns.…”
Section: Residential Plumbing Design and Operationmentioning
confidence: 99%
“…The purpose of this study was to identify optimal combinations of in-building disinfectants and pipe materials that limit the proliferation of multiple OPPPs and ARGs in premise plumbing. We used convectively mixed pipe reactors (CMPRs), consisting of three pipe materials (PVC, copper, and iron), for replicated simulation of the distal reaches of premise plumbing and evaluation of the effects of chlorine, chloramine, chlorine dioxide, and copper–silver disinfectants. P. aeruginosa and A. baumannii were inoculated into the CMPRs as two representative OPPPs that are prominent agents of antibiotic-resistant , and nosocomial infections that are also resistant to disinfectants. ,, After incrementally increasing disinfectant doses over a period of several weeks, disinfectants were removed to characterize the regrowth patterns.…”
Section: Introductionmentioning
confidence: 99%